Hydrological System Complexity Induces a Drought Frequency Paradox - Buitink, Joost; van Hateren, Theresa C.; Teuling, Adriaan J. (Frontiers in Water, 2021)
Droughts occur as a result of a lack of water compared with normal conditions. Whilst this appears trivial, the exact drought definition of drought is not. Especially as different drought types are present, resulting from the different variables in a hydrological system, each with unique characteristics. We use a common drought definition, the percentile score, and apply the same definition across all drought types, to study whether the actual occurrence of droughts matches the definition. We focus on the data-rich Dutch province of Gelderland, to study droughts from observations across five major components of the terrestrial hydrological cycle. When a percentile threshold of 20% is used as drought definition, corresponding to a mild drought, droughts anywhere in the system occur at least 3 times more frequently (73% of the time). On the other hand, the situation where drought occurs across all components of the terrestrial hydrological cycle is more than 4 times less likely than the drought threshold of 20% (namely 5% of the time). This can be attributed by both (1) the different responses across the hydrological system, and (2) the spatial variability present within each component of the hydrological system. With this study, we show the existence of the drought frequently paradox: although droughts are seen and defined as rare from a scientific perspective, when viewed from a societal or operational water management perspective in typical hydrological systems subject to spatial variability and other system complexity, droughts become common, rather than rare. This paradox is a consequence of an inconsistent use of the percentile score drought definition between research and operational water management, and better communication between the two domains is needed in search for a universally accepted drought definition.